Microsatellite-Based Genetic Structure and Diversity of Local Arabian Sheep Breeds - Al-Atiyat, Raed M.; Aljumaah, Riyadh S.; Alshaikh, Mohammad A.; Abudabos, Alaeldein M. (Frontiers in Genetics, 2018)
The genetic diversity of the sheep breeds in the Arab countries might be considered to be a mirror of the ecology of the region. In this study, the genetic structure and diversity of sheep breeds from Saudi Arabia (Harri, Najdi, Naemi, Arb and Rufidi) and Awassi sheep from Jordan as an out-group were investigated using 19 microsatellites. All the breeds had high intra-population genetic diversity expressed as allelic number (7.33) and richness (2.9) and, expected heterozygosity (0.77). Structure analysis revealed three main gene pools underlying the ancestral genetic diversity of the study populations. The first pool had Harri, Najdi and Rufidi breeds; the second had Naemi and Awassi breeds, and the third had the Arb breed which was significantly differentiated from the other breeds. Factorial correspondence analysis lent further support to the presence of the three gene pools. Although the outgroup Awassi sheep was more clearly differentiated, it still genetically close to Naemi sheep. The differentiation of the Arb breed could have been resulted from geographic and reproductive isolation. On the other hand, the genetic structure of the other two gene pools could be the result of the past and recent gene flow between individuals reared in the region known to be the center for animal husbandry and trading until the current time.